2017
DOI: 10.1186/s13613-017-0309-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators of survival and survival prediction model following extracorporeal cardiopulmonary resuscitation in patients with sudden refractory cardiac arrest

Abstract: BackgroundExtracorporeal cardiopulmonary resuscitation (ECPR) has been considered in selected candidates with potentially reversible causes during a limited period. Candidate selection and the identification of predictable conditions are important factors in determining outcomes during CPR in the emergency department (ED). The objective of this study was to determine the key indicators and develop a prediction model for survival to hospital discharge in patients with sudden cardiac arrest who received ECPR.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 41 publications
2
32
1
1
Order By: Relevance
“…Several studies have sought to determine the factors associated with positive outcomes from ECPR, with varying results. While there is considerable prognostic factor heterogeneity between studies, a short ‘low flow time’, and an initial shockable rhythm, were most consistently associated with improved outcomes . Prehospital ECPR initiation potentially minimises this circulatory low flow time and has also been associated with significantly increased rates of ROSC .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have sought to determine the factors associated with positive outcomes from ECPR, with varying results. While there is considerable prognostic factor heterogeneity between studies, a short ‘low flow time’, and an initial shockable rhythm, were most consistently associated with improved outcomes . Prehospital ECPR initiation potentially minimises this circulatory low flow time and has also been associated with significantly increased rates of ROSC .…”
Section: Discussionmentioning
confidence: 99%
“…Group 2 patients had an initial rhythm of pulseless electrical activity (PEA) and had no sustained ROSC with the next rhythm check. While non‐shockable rhythms have often been excluded from ECPR protocols, SAMU de Paris have now included PEA in a prehospital ECPR protocol, and some studies have found this initial rhythm to be a prognostic indicator of survival . Group 3 patients did not satisfy Group 1 or 2 inclusion criteria but had some characteristics that have been associated with positive outcomes after ECPR, such as initial shockable rhythm or transient ROSC .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations